Using Java to generate globally unique identifiers for DICOM objects. - Kamauu AWC; DuVall SL; Avrin DE (Journal of Digital Imaging, 2009)
Digital imaging and communication in medicine (DICOM) specifies that all DICOM objects have globally unique identifiers (UIDs). Creating these UIDs can be a difficult task due to the variety of techniques in use and the requirement to ensure global uniqueness. We present a simple technique of combining a root organization identifier, assigned descriptive identifiers, and JAVA generated unique identifiers to construct DICOM compliant UIDs.